The Effects of Parental Literacy Involvement and Child Reading Interest on the Development of Emergent Literacy Skills - (:unkn) unknown (My University, 2013)
Acquisition of literacy is best conceptualized as a developmental continuum, with its origins early in the life of a child, rather than an all-or-none phenomenon that begins when children start school. How parents expose their children to literacy even before they enter school is important for the later development of reading. The home environment is an important setting for the acquisition of literacy knowledge because children have unique literacy opportunities at home such as observing literacy activities of others, engaging in joint reading and writing activities with other people, and benefiting from teaching strategies used by family members. Researchers suggest that storybook exposure and parental teaching about literacy are distinct types of activities that differently promote language skills and the acquisition of early literacy skills. This study used hierarchical regression analyses to examine the role of storybook exposure and direct parental teaching of emergent literacy in addition to child interest of reading and literacy activities to predict emergent literacy outcomes using an ethnically diverse sample of preschool aged children from low socio-economic status (SES) backgrounds. The study found that young children's book exposure predicts oral language development. This has important implications for parental involvement in children's education.
Keywords: Child Literacy Interest; Emergent Literacy; Home Literacy Environment; Parent Literacy Teachings; Shared Book Reading